Design of Portable Optical Vein Finder - Ahmed, Ahmed Husam Uldeen; Abdelbaqi, Ahmed Youns; Zedan, Zakaria Jamal; Alwan, Maryam Hussein; Loqman, Ibrahim Mohamed (American Journal of Biodiversity, 2025)
Several people are unlucky with veins that are hard to stick. Some of them just have small veins that are hard to feel for and hard to get a needle into, other fat people tend to have their veins buried deeper and are thus harder to find. In this case, phlebotomists need several tries to find the vein and stick it properly, wasting their time and effort, and creating pain to these patients. This project aims to build a portable vein finder, that uses visible and near infrared radiations (NIR)light. The system will help the phlebotomists to explore the vein easily by applying a visible and NIR wavelengths on the patient’s arm.it will use processing unit to control light intensity to provide the phlebotomists with the place of the patients vein within a one seconds. Hence, reducing the patient pain, and saving phlebotomists effort and time.